Contribution of Job Enrichment and Delegation of Authority Towards Educational Implementers' Work Motivation - Yasril, Yasril; Marwan, Syaiful (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2026)
Everyone agree that improving the performance of educational implementers through job enrichment and delegation of authority will increase company productivity. However, the facts show that these two management elements must work as expected in the Department of Education and Culture to effectively enhance employee motivation and engagement, which are crucial for achieving the desired increase in company productivity. The purpose of this study is to determine how delegation of authority and job enrichment affect the desire to work. There are three hypotheses tested in this study. First, job enrichment affects the desire of implementers to work in schools; second, delegation has an impact on influencing the desire of implementers to work in schools; and third, job enrichment and delegation of authority simultaneously affect the desire of implementers to work in schools. This study involved 140 educational implementers from the Department of Education and Culture of Tanah Datar Regency, along with 57 samples selected randomly based on the proportion of education level, class, and length of service. The research method was carried out using a quantitative approach. The research was collected using a questionnaire with a Likert scale model, which has been tested for reliability and validity. The results of the data analysis show that the contribution of job enrichment to the work motivation of educational implementers is 16%, the contribution of official delegation to the work motivation of educational implementers is 28.09%, and the contribution of job enrichment and official delegation to the overall work motivation of educational implementers is 42%. It is hoped that this research will be useful for future research.